How far ethics education positively influences ethical decision making of the young lawyers in Kedah? / Anida Mahmood, Haswira Nor Mohamad Hashim and Kamarul Ariffin Mansor - Mahmood, Anida; Mohamad Hashim, Haswira Nor; Mansor, Kamarul Ariffin (Institute of Research, Development and Commercialization (IRDC), 2007)
This paper was written based on part of the findings of a survey made on young lawyers who are practicing in the state of Kedah. Young lawyers are advocates and solicitors with less than seven y ears of active practice. The objective of this study is to determine what factors positively influenced young lawyers' ethical decision making. Data was collected from /33 young lawyers who are practicing in the state of Kedah between January - June 2006 through self-administered and close- end questionnaires. The finding suggests that knowledge in professional legal ethics gained at the law faculty, pupil age and short ethics course does not contribute much to the ethical decision making of the young lawyers. Moved by this finding. this paper attempts to discuss the current legal ethics education in Malaysia. The main contention of the writers is their firm belief that the current practice of professional legal ethics education in Malaysia is insufficient and far from being adequate in producing ethical lawyers. Therefore the writers have proposed for professional legal ethics education in Malaysia to be reformed and this proposal serves as the basic premise of this paper.